Health Care Transformation in Contemporary China Moral Experience in a Socialist Neoliberal Polity - Tu, Jiong; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This multifaceted book examines the free market reform of the Chinese healthcare system in the 1980s and the more collectivist or socialist counter-reforms that have been implemented since 2009 to remedy some of the problems introduced by marketization. The book is based on an ethnographical study in a Chinese county from 2011 to 2012, which investigated local people's experience of healthcare reforms and the various ways in which they have adapted their own behavior to the constraints and opportunities introduced by these reforms. It provides a vivid depiction of the morality and emotionality of people's experiences of the Chinese healthcare system and the myriad frustrations and sometimes desperation it induces not only among patients with significant health problems and their families, but also healthcare practitioners caught between their desire to do right by their patients and the penalties they personally incur if they do not adhere to institutionalized cost-saving measures. The people's experiences within China's health sector presented reflect many similar experiences in the wider Chinese society. The book is thus a valuable resource for researchers and graduate students interested in China's healthcare reforms and scholars concerned with issues of contemporary Chinese society. .
Abstract -- Illustrations -- Notes -- Introduction: The Politics and Morality of Health Care Transformation in China -- Rescue First or Money First? Commercialised Institutions, Calculating Professionals, and Neoliberal Governance -- From 'Care of the Self' to 'Entrepreneur of the Self': Reconfiguration of Patients' Responsibilities, Needs, and Rights -- Health Insurance Regime as Differentiation and Discipline -- Gift Practice in the Chinese Health Sector: Inequality, Power and Governance -- Power Game of Nao: Violent Disputes in the Chinese Medical Sector -- Practice of the Self: 'Barefoot Doctors' in Post-reform China -- Conclusion: Moral Experience in a Socialist Neoliberal Polity -- References -- Appendix I -- Appendix II -- Appendix III -- Appendix IV.
Keywords: Social medicine; Medical care; Ethnology; Medical Sociology; Health Care; Ethnography